Impact of COVID-19 Stay-At-Home Restrictions on Falls in One Community of High-Risk Older Adults. (May 2022) - McIntyre, Cecily C.; Prichett, Laura; McNabney, Matthew K.
Aim: To examine the relationship between falls among high-risk older adults at one Program of All-Inclusive Care for the Elderly (PACE) and the COVID-19 closure of its Day Health Center (DHC), which provides participants with social and rehabilitative services and contributes to their weekly physical activity. Methods: Self-reported falls during the 3 months before the DHC's closure ("pre–COVID-19") were compared in number and in character to falls during its closure ("COVID-19"). Results: One thirty five participants were enrolled during the entire 6-month period; 37% ( n = 50) fell during this time. These participants experienced fewer falls during COVID-19 (mean = 0.64) than they did pre–COVID-19 (mean=1.24, p = .0003). Conclusions: In this population of high-risk, community-dwelling older adults, an abrupt reduction in activity levels may have reduced falls. Physical activity has been shown to both increase and protect against falls in older adults. The long-term consequences of a comparably prolonged period of inactivity merit further study.